2017
DOI: 10.9778/cmajo.20160166
|View full text |Cite
|
Sign up to set email alerts
|

Access to hyperacute stroke services across Canadian provinces: a geospatial analysis

Abstract: Background: Canada's vast geography creates challenges for ensuring prompt transport to hospital of patients who have had a stroke. We sought to determine the proportion of people across various Canadian provinces for whom hyperacute stroke services are accessible within evidence-based time targets. Methods:We calculated, for the 8 provinces with available data, drive-time polygons on a map of Canada that delineated the area around stroke centres and emergency medical services (EMS) base centres to which one c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Previous studies evaluating geographic access to stroke services have estimated that over 80% of the US population has access to thrombolysis-capable hospitals within 60 minutes, with similar results seen in Ontario and other Canadian provinces. 10,12,19 However, these studies assessed the entire population rather than rural communities, where access might be anticipated to be lower. Our finding that over 81% of rural residents lived within 60 minutes of driving time to thrombolysis centers provides evidence of very good rural access to this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies evaluating geographic access to stroke services have estimated that over 80% of the US population has access to thrombolysis-capable hospitals within 60 minutes, with similar results seen in Ontario and other Canadian provinces. 10,12,19 However, these studies assessed the entire population rather than rural communities, where access might be anticipated to be lower. Our finding that over 81% of rural residents lived within 60 minutes of driving time to thrombolysis centers provides evidence of very good rural access to this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous geospatial analyses have provided important information on access to stroke care across Ontario and Canada, but did not specifically evaluate access to care for rural residents. [10][11][12] We aimed to quantify geographic access to stroke care for rural residents of Ontario, Canada, using linked population-based administrative data sources to estimate the proportion of people in rural communities who were within 30, 60, and 240 minutes of travel time by car (at posted speed limits) from stroke care services, including neuroimaging, thrombolysis, EVT, stroke unit care, stroke prevention clinics, and inpatient rehabilitation facilities.…”
Section: Introductionmentioning
confidence: 99%
“…As the first step in understanding accessibility to healthcare services for Australian stroke survivors, this study applied Geographic Information System (GIS) techniques to map and then examine the spatial distribution of primary healthcare services in one Primary Health Network (PHN) in South-East Queensland to determine whether these services are located in geographically accessible areas relative to the discharge location of patients with stroke. Internationally, GIS technology was recently used in Canada to determine the drive time for accessibility to stroke centres and emergency medical services for hyperacute stroke management (Eswaradass, Swartz, Rosen, Hill & Lindsay, 2017), with the researchers concluding that most Canadians live within 6-h road access of stroke centres and emergency medical services. A second study exploring stroke prevention services (services that provide assessment and intervention to minimise the risk of subsequent stroke) in Canada found that just over 87% of Canadians can access a stroke prevention service within a 1-hour drive time (Jewett et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Acute ischemic stroke (AIS) is the most common type of stroke, accounting for about 80% of the total cerebral apoplexy [ 1 ]. It is the third leading cause of death worldwide.…”
Section: Introductionmentioning
confidence: 99%